2001
DOI: 10.1053/euhj.2000.2247
|View full text |Cite
|
Sign up to set email alerts
|

Does early repolarization in the athlete have analogies with the Brugada syndrome?

Abstract: Early repolarization is almost always the rule in athletes but it is also frequent in sedentary males. Tracings somewhat simulating the Brugada syndrome were observed in only 8% of athletes without a history of syncope or familial sudden death. Significant differences exist between athletes with early repolarization and patients with the Brugada syndrome as regards the amplitude of ST elevation and QRS duration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
38
1
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(52 citation statements)
references
References 15 publications
9
38
1
1
Order By: Relevance
“…11 In order to distinguish the normal ST segment elevation observed in athletes from that of Brugada syndrome, the magnitude of the ST elevation and the QRS duration may be useful. 8 Therefore, not only ST segment elevation, but also the S wave width should be measured to detect high-risk patients and we propose an S wave width in V1 ≥0.08 s and ST segment elevation ≥0.18 mV as new criteria for high-risk Brugada syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 In order to distinguish the normal ST segment elevation observed in athletes from that of Brugada syndrome, the magnitude of the ST elevation and the QRS duration may be useful. 8 Therefore, not only ST segment elevation, but also the S wave width should be measured to detect high-risk patients and we propose an S wave width in V1 ≥0.08 s and ST segment elevation ≥0.18 mV as new criteria for high-risk Brugada syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…4 On the other hand, symptomatic patients often need an implantable cardioverter defibrillator (ICD) because of a high incidence of recurrence. 5,6 Recent reports 7,8 have suggested an important contribution of intraventricular conduction delay to the onset of lethal ventricular arrhythmias and so we hypothesized that there might be some findings on the standard 12-lead electrocardiogram (ECG) reflecting intraventricular conduction delay that could be used to distinguish highand low-risk patients. In order to clarify the ECG characteristics that could be useful for the diagnosis of high-risk Brugada syndrome, we reviewed 12-lead ECGs from the Japanese Brugada syndrome registry.…”
mentioning
confidence: 99%
“…Between 40 and 80% of endurance athletes exhibit abnormal resting 12-lead echocardiograms (ECGs). [74][75][76] Abnormal ECGs were found to be more common in male than female athletes. 77,78 Of the abnormalities detected in athletes of both sexes, the most common findings were Q waves, T-wave inversions, left-axis deviation, ST depression, and prolonged QTc.…”
Section: Sudden Cardiac Deathmentioning
confidence: 99%
“…Sharma et al (1999) found that almost half of elite junior athletes had voltage criteria for left ventricular hypertrophy. ST segment elevation soon after the QRS complex, known as 'early repolarization', appears to be a normal feature of the ECG in athletes (Bianco et al 2001). In a study of repolarization in over 1200 athletic students, Bjornstad et al (1994) found that the mean QRS-T angle was significantly greater in athletes, and U waves were more prominent.…”
Section: Ecg Abnormalities In Athletesmentioning
confidence: 99%